Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/978-3-642-15892-6_28
|View full text |Cite
|
Sign up to set email alerts
|

Bossy or Wimpy: Expressing Social Dominance by Combining Gaze and Linguistic Behaviors

Abstract: Abstract. This paper examines the interaction of verbal and nonverbal information for conveying social dominance in intelligent virtual agents (IVAs). We expect expressing social dominance to be useful in applications related to persuasion and motivation; here we simply test whether we can affect users' perceptions of social dominance using procedurally generated conversational behavior. Our results replicate previous results showing that gaze behaviors affect dominance perceptions, as well as providing new re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The first is to validate whether our virtual recruiter can express input attitudes correctly. We also wanted to compare the respective contributions of the non-verbal and verbal modalities to the expression of attitudes, in order to verify previous results indicating that combining both modalities achieves the best results when expressing attitudes [69], [96]. Finally, we investigated whether the perception of attitudes is similar when participants watch videos of the virtual recruiter compared to when they directly interact with it.…”
Section: Virtual Recruiter Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is to validate whether our virtual recruiter can express input attitudes correctly. We also wanted to compare the respective contributions of the non-verbal and verbal modalities to the expression of attitudes, in order to verify previous results indicating that combining both modalities achieves the best results when expressing attitudes [69], [96]. Finally, we investigated whether the perception of attitudes is similar when participants watch videos of the virtual recruiter compared to when they directly interact with it.…”
Section: Virtual Recruiter Evaluationmentioning
confidence: 99%
“…This dialogue act is then transformed by the Dialogue model into an FML file, consisting of a sentence to utter enriched by communicative function tags. For a same dialogue act, the wording can influence the expressed attitude [96]; thus, we chose to use the Dialogue model of Callejas et al [69], which uses a set of FML files for the expression of social attitudes in job interview scenarios, for unfriendly, neutral and friendly attitudes. We extended this collection of FML files to include dominant attitudes using the guidelines described in [97].…”
Section: Virtual Recruiter Architecturementioning
confidence: 99%
“…Many studies use a within-subjects design where participants are shown multiple agents with different target personality traits, including those that are meant to be the opposites of each other (e.g. extraverted and introverted) [6,8,19,22,44,48]. While this method maximizes statistical power and is more logistically efficient, a within-subjects design may introduce unintended contrast effects.…”
Section: Contrast Effectsmentioning
confidence: 99%
“…Personality in virtual agents can be expressed through a number of different cues, such as language usage [13,[16][17][18], facial expression [6,8,[19][20][21], and non-verbal behaviors such as gesture and posture [6,18,22,23]. For example, extraversion is associated with a faster rate of speech and larger gestures, so agents portraying extraversion talk faster and gesture with wider arms than agents portraying introversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation